Recent trends in United States temporary foreign workers in Canada - Feng Hou; Yuqian Lu (Economic and Social Reports)
The movement of temporary foreign workers between the United States and Canada represents a critical yet understudied aspect of North American labour mobility. This article examines recent trends in the number of temporary foreign workers from the U.S. to Canada, their employment patterns, industrial distribution and earnings.